Modification of the submandibular gland transfer procedure. (12th May 2016) - Marzouki, Hani Z.; Elkhalidy, Youness; Jha, Naresh; Scrimger, Rufus; Debenham, Brock J.; Harris, Jeffrey R.; O'Connell, Daniel A.; Seikaly, Hadi
Abstract : Objectives/Hypothesis: The treatment for most advanced head and neck cancers (stage III and IV) usually includes radiation, and the most common side effect of this treatment modality is a permanent decrease in salivary production. Xerostomia is a devastating complication that significantly affects patients' quality of life by interfering with functions of taste, mastication, deglutition, and speech production. Treatment of xerostomia is varied, but one of the strategies developed by our group was to preserve one submandibular gland by surgically transferring it to the submental space and shielding it from the full dose of radiation. This procedure is proven to reduce the rate of radiation‐induced xerostomia, but its main disadvantage is that it is contraindicated in oral cavity cancer. This study describes and evaluates a modification of the submandibular gland transfer (SGT) procedure, where the submandibular gland contralateral to the disease process is relocated to the parotid region. This modification has the potential of expanding the benefits of submandibular gland transfer procedures to patients with oral cavity cancers. Study Design: Prospective feasibility study. Methods: This study involved nine patients with a new diagnosis of advanced head and neck cancer undergoing major head and neck cancer resection with postoperative adjuvant radiation therapy. The new modified salivary gland transfer procedure was performed on all nine patients, and the glands total dose received with radiation therapy was assessed. Results: All the modified SGT procedures were successful with no post‐operative complications. The radiation oncology team has been able to successfully localize the transferred submandibular glands and shield them from the radiation beam postoperatively. Conclusions: We have successfully demonstrated that surgical transfer of a submandibular salivary gland to the parotid region is feasible, surgically viable, oncologically sound, and does not interfere with radiation therapy. Level of Evidence: 4 Laryngoscope, 126:2492–2496, 2016